(untitled) (International journal of artificial intelligence, 2024)
The information dealing with the life and his literary activity can be found in memorials of Alisher Navoi (1441-1501), the great classical poet and founder of Uzbek language and literature. There were not any other riliabce notes done by men of literary activity concerning the life of the poet, e[cept Navoiy’s works. We can say that Mavlono Gadoiy’s life and his literary legacy has been taken as the subject of discussion since the beginning of XX century.